So few of me - Reynolds, Peter 1961- (Walker Books, 2006)
Leo is a busy lad. So much to do. So little time. If only there were two of him, or three, or four, or even MORE ...--Cover
First published by Candlewick Press in 2005
Keywords: Self-perception / Pictorial works / Junior fiction; Conduct of life / Pictorial works / Junior fiction; Cloning / Pictorial works / Junior fiction; Work / Psychological aspects / Pictorial works / Junior fiction; Counting / Pictorial works / Junior fiction; Self-perception / Juvenile fiction; Conduct of life / Juvenile fiction; Cloning / Juvenile fiction; Work / Juvenile fiction; Psychologie; Faulheit; Fleiß; Selbsterziehung; Selbstbild; Zählen; Bilderbuch